Rethinking the Application of the Difference Principle in Arrangements for the Distribution of Job Loss Benefits - Ratih Dheviana Puru Hitaningtyas; M. Hadi Subhan; Lanny Ramli; Nurwahjuni Nurwahjuni (Faculty of Law, Universitas Pekalongan, 2023)
The philosophy of organizing labor social security aims to protect workers from socio-economic risks resulting from involuntary loss of income. This includes providing protection during and after the employment relationship. Job Loss Insurance (JKP) under the National Social Security System (SJSN) is designed to offer protection to workers experiencing Termination of Employment (PHK), but workers who resign voluntarily are not entitled to benefits under Article 19 in conjunction with Article 20 of Permenaker No. 37/2021. This paper proposes reinterpreting the concept of termination and applying the Difference Principle to extend JKP benefits to workers who resign involuntarily (Constructive Dismissal) in line with the principles of organizing social security.